Áreas e volumes : uma abordagem complementar ao livro "A matemática do ensino médio" SBM - vol 2, E. L. LIMA, et al. - Menezes, José Claudemir de (2015)
In this work we are treated in detail, three subjects of mathematics that relate to each other: Plane Geometry, Geometry and Spatial Revolution Solid. In this approach, we prioritized the calculation of the area of the lateral surfaces and full of Prism, Pyramid, Cylinder, Cone and Sphere, and the calculation of its volumes in the latter, using the principle of the deduction Cavalieri their formulas. In the study of Revolution Solids, we highlight the theorems of Pappus, used to derive the formulas of surface areas and volumes of cylinder, cone and revolution sphere.